(untitled) (Journal Of Educational and Psychological Researches, 2018)
Generally, the academic facilities necessitate specific criteria to be under the regional standards such as creative leaders, and a positive climates that induce to create an organizational culture within the academic institution. Consequently, these variables promote to improve the educational and administrative performance pursuing to achieve the general objectives. Thus, the current research aims to explore the level of privileged organizational culture among Baghdad University Colleges, explore the administrative creativity of deans and their assistants in addition to identify the relationship between them. The researchers prepared two instruments which were distributed among (70) individual of the targeted sample to collect the required data.